Income generating activity in higher education: A case study of a public university in Indonesia - Amir Mahmud; Agus Nuryatin; Nurdian Susilowati (International Journal of Evaluation and Research in Education (IJERE), 2022)
This study aimed to identify the income-generating activities and explore its management model using the case study method. In-depth interviews and documentation were used to collect data. The sample used purposive sampling from 26 study programs. Government subsidy, which is meant to cater to tuition and operational expenses, has been inadequate. Therefore, activities in the laboratory can be optimized as an income generator. The results of mapping activities in the laboratory and study programs are seminars, conferences, workshops, building rent, ballroom rent, laboratory services, vehicle rent, and scientific consulting services. Income-generating supplemented the budget of the university. The income is beneficial to hire additional project personnel, purchase supplies, materials and equipment, and improve facilities needed for instruction, research, extension, training, and productive activities. The development pattern of income-generating management through partnership and cooperation between the rector, head of the business development agency, deans, and head of a study program also laboratory so that all forms of activities that become financial sources can be monitored and evaluated. Moreover, the preparation of the accountability report must be transparent and accountable.